An Investigation into School Leaders' Perspective as Change Agents in the Implementation of the Performance Management System (PMS): Case of South East and Southern Regions' Junior Secondary Schools in Botswana - Molefhi, Thapelo; Pheko, Bolelang (African Journal of Education and Practice, 2023)
Purpose: This background or concept paper develops a case into school leaders' perceptions as change agents in the implementation of the performance management system (PMS) in Junior Secondary Schools in Botswana. As change agents, school leaders were expected to fully implement the PMS. Research has demonstrated that PMS has been unsatisfactorily implemented in Junior Secondary Schools in Botswana (Koruyezu, 2010; Bulawa, 2011; Nkwe, 2015; Molefhi, 2015, Pheko, Bathuleng & Kgosidialwa, 2018). The purpose of this paper is to lay the foundation for the study which will investigate school leaders' perceptions as change agents in the implementation of the performance management system (PMS) in the South East and Southern Regions' junior secondary schools in Botswana. Methodology: The study plans to use the quantitative research approach to explore school leaders' perceptions as change agents in implementing PMS in their schools. A Likert scale questionnaire for data collection from school heads, deputy school heads, heads of department and senior teachers will be employed. This background paper draws from transformational leadership theory to outline an agenda and approach for change agent leadership. Findings: This is an empirical study whose findings will establish views from school leaders on what issues they encountered while implementing PMS. Furthermore if objectives of this policy have been implemented and achieved. From the findings it will be succinctly clear what change attributes school leaders as change agents require in order to effectively implement the PMS. Recommendations will be developed to assist the Ministry of Education Skills and Development on better alternatives of implementing PMS policy including meeting the skills of school leaders to become effective change agents. Unique Contribution to Theory, Practice and Policy: as a practice school leaders are mandated to ensure that any approved change for the schools meet the agreed objectives, but there is no study that have focused on the perceptions of the school leaders with regard to this. It is therefore crucial for this proposed study to indicate what type of policy would be appropriate to show the necessary skills required for the implementation of the PMS in the schools. This approach is validated by the transformation theory. Therefore, its unique contribution would be to bring forth the necessity for school leaders to have the requisite change attributes.